Optimising growth performance, nutrients digestibility, immunity and gut health in broilers through ginger-derived phyto-protease enzyme (zingibain) supplementation - Ahmad Khan; Asad Sultan; Ziaul Islam; Muhammad Shahkar Uzair; Ibrahim A. Alhidary; Rifat Ullah Khan; Shabana Naz; Naseer Khan Momand; Ruchi Tiwari (Italian Journal of Animal Science)
This study investigated the impact of ginger-derived phyto-protease enzyme on growth performance, immunity, gut health and nutrient digestibility in broilers. A total of 360 day-old broiler chickens were randomly assigned to four treatments with six replicates each: a control group (T1) and groups supplemented with 50 g/ton (T2), 100 g/ton (T3) and 150 g/ton (T4) of the enzyme. Over a 35-day period, birds were provided with free access to feed and water under controlled conditions. The highest feed intake was observed in T3 during the second week, while T4 showed the lowest intake overall. Body weight gain was significantly highest in T4, demonstrating enhanced growth performance. Feed conversion ratio (FCR) was lowest in T4, indicating improved feed efficiency. Carcase quality analysis revealed higher dressing percentages and organ weights (bursa, spleen and thymus) in T4 compared to the control. Gut pH levels were significantly lower in T3 and T4 across different segments of the gastrointestinal tract, enhancing nutrient absorption. Antibody titres against Newcastle disease virus were significantly higher in T4 on days 21 and 35, indicating improved immunity. Histomorphological analysis of the intestines showed increased villus height and width in T4, with reduced crypt depth, further supporting enhanced nutrient absorption. These findings suggest that the highest inclusion rate of ginger-derived phyto-protease enzyme (150 g/ton) optimally enhances growth performance, immunity, gut health and nutrient digestibility in broilers. This study highlights the potential benefits of incorporating ginger-derived phyto-protease in poultry diets to improve overall health and performance.